2023
DOI: 10.1111/csp2.12942
|View full text |Cite
|
Sign up to set email alerts
|

Redefining rights‐based conservation through philanthropy: The Ford Foundation in Mesoamerica

Laura Aileen Sauls,
Victor López Illescas

Abstract: The role of the philanthropic sector in climate change mitigation and biodiversity conservation is gaining renewed attention as new pledges to dramatically increase funding for nature-based climate solutions mount. Despite their significant role in the conservation space, philanthropies are relatively understudied as donors; in particular, the lack of accountability and transparency in philanthropy have made them a "black box", including in conservation-related efforts. Based on extensive document and database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…They found a "clear level of transparency" already in the work and priorities of US foundations supporting sustainable seafood but also show how vague descriptions of grants still pose a barrier to more nuanced understanding of funding objectives and end recipients (Schiller et al, 2023). Sauls and L opez Illescas (2023) describe how the Ford Foundation shifted their strategy over time to center Indigenous Peoples and local communities in grant-making for rights-based conservation in Mexico and Central America. As support for Indigenous-led conservation gains traction within mainstream conservation philanthropy globally, this articlecoauthored by a current Ford Foundation program officer-provides a detailed example of how one foundation actually made this change in practice.…”
Section: Funding Flowsmentioning
confidence: 99%
“…They found a "clear level of transparency" already in the work and priorities of US foundations supporting sustainable seafood but also show how vague descriptions of grants still pose a barrier to more nuanced understanding of funding objectives and end recipients (Schiller et al, 2023). Sauls and L opez Illescas (2023) describe how the Ford Foundation shifted their strategy over time to center Indigenous Peoples and local communities in grant-making for rights-based conservation in Mexico and Central America. As support for Indigenous-led conservation gains traction within mainstream conservation philanthropy globally, this articlecoauthored by a current Ford Foundation program officer-provides a detailed example of how one foundation actually made this change in practice.…”
Section: Funding Flowsmentioning
confidence: 99%
“…Assumptions about philanthropic foundations are made by practitioners and academics alike, with their role as agents who have the capacity to change and reflect too often denied. A recent study on the Ford Foundation showed how since the 2000s, it has radically transformed its donor practices through the agency of its staff and now funds indigenous environmental grass-roots and rightsbased movements (Sauls & López Illescas, 2023). As the black box of philanthropy opens, conservation directors and managers should better engage them on issues of conservation injustice.…”
Section: Powerful Actors' Responsibilities Going Beyond Selling Succe...mentioning
confidence: 99%